Glucocorticoid Receptor-Deficient Foxp3+ Regulatory T Cells Fail to Control Experimental Inflammatory Bowel Disease - Rocamora-Reverte, Lourdes; Tuzlak, Selma; von Raffay, Laura; Tisch, Marcel; Fiegl, Heidi; Drach, Mathias; Reichardt, Holger M.; Villunger, Andreas; Tischner, Denise; Wiegers, G. Jan (Frontiers in Immunology, 2019)
Activation of the immune system increases systemic adrenal-derived glucocorticoid (GC) levels which downregulate the immune response as part of a negative feedback loop. While CD4+ T cells are essential target cells affected by GC, it is not known whether these hormones exert their major effects on CD4+ helper T cells, CD4+Foxp3+ regulatory T cells (Treg cells), or both. Here, we generated mice with a specific deletion of the glucocorticoid receptor (GR) in Foxp3+ Treg cells. Remarkably, while basal Treg cell characteristics and in vitro suppression capacity were unchanged, Treg cells lacking the GR did not prevent the induction of inflammatory bowel disease in an in vivo mouse model. Under inflammatory conditions, GR-deficient Treg cells acquired Th1-like characteristics and expressed IFN-gamma, but not IL-17, and failed to inhibit pro-inflammatory CD4+ T cell expansion in situ. These findings reveal that the GR is critical for Foxp3+ Treg cell function and suggest that endogenous GC prevent Treg cell plasticity towards a Th1-like Treg cell phenotype in experimental colitis. When equally active in humans, a rationale is provided to develop GC-mimicking therapeutic strategies which specifically target Foxp3+ Treg cells for the treatment of inflammatory bowel disease.